Acute effect of 10-minute jogging as warm-up on mechanical properties of triceps surae muscle and skin temperature in track-and-field athletes - Meerits, T.; Bacchieri, S.; Pääsuke, M.; Ereline, J.; Cicchella, A.; Gapeyeva, H. (Medicina dello Sport, 2018)
BACKGROUND: The aim of the study was to evaluate acute effect of 10-minute jogging on a treadmill as warm-up on mechanical properties and skin temperature of triceps surae (TS) muscle. METHODS: Twelve power-trained track-and-field male athletes aged 18-25 years voluntarily participated in the study. The mechanical properties (tone, elasticity, stiffness and relaxation time) of TS muscle were measured by MyotonPRO device immediately before and after standard jogging exercise. The skin temperature of TS muscle was recorded simultaneously throughout the study. RESULTS: Muscle tone of TS increased up to 6.8% (P<0.001) and stiffness up to 6.7% (P<0.001) after jogging and elasticity characteristics improved by 13.3% (P<0.001). Relaxation time of TS muscle shortened by 9.2% (P<0.001). Following the jogging the skin temperature raised by 3.9% for TS muscle (P<0.001). There were no significant association between changes of skin temperature and mechanical properties of TS muscle. CONCLUSIONS: Ten-minute jogging as warm-up improves significantly TS muscle elastic parameters (elasticity and relaxation time) and raises skin temperature of TS muscle.